2015
DOI: 10.5812/jjm.19238
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Delay in Diagnosis and Treatment of Pulmonary Tuberculosis

Abstract: Background:Early treatment of pulmonary tuberculosis (PTB) is necessary for a successful tuberculosis (TB) control program.Objectives:The objective of this study was to determine total treatment delay and its associated factors among PTB patients in Ahvaz.Patients and Methods:A retrospective study was performed among newly diagnosed PTB cases registered in 2010 at the Ahvaz health center. Total treatment delay was defined as the time interval between the onsets of cough to the initiation of anti-TB treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 15 publications
6
19
1
2
Order By: Relevance
“…The findings from our study on pathways to care for TB in vulnerable urban settings in Mumbai, generally complement the findings of several studies undertaken in India [ 27 , 28 , 29 ] and elsewhere [ 30 , 31 , 32 , 33 ]. The largest contributor to the total duration of 65 days extending from the beginning of symptoms to the initiation of treatment, as reported by patients, was the time spent on obtaining the diagnosis of TB.…”
Section: Discussionsupporting
confidence: 85%
“…The findings from our study on pathways to care for TB in vulnerable urban settings in Mumbai, generally complement the findings of several studies undertaken in India [ 27 , 28 , 29 ] and elsewhere [ 30 , 31 , 32 , 33 ]. The largest contributor to the total duration of 65 days extending from the beginning of symptoms to the initiation of treatment, as reported by patients, was the time spent on obtaining the diagnosis of TB.…”
Section: Discussionsupporting
confidence: 85%
“…We found 11 studies had a low risk of bias (16,19-25a-25d), 7 had a moderate risk of bias (17,(26)(27)(28)(29)(30)(31) and 5 had a high risk of bias (18,(32)(33)(34)(35) (Tables 1,2). We considered the WHO report as a single study with coverage of 4 countries that met our inclusion criteria (25).…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 84%
“…At least one factor attributing to patient delay was analysed in 10 studies (16,(18)(19)(20)(21)(22)(23)(24)(25)35). Studies mostly assessed predisposing factors such as patient sociodemographic characteristics, TB knowledge and perception about TB.…”
Section: Factors Associated With Patient Delaymentioning
confidence: 99%
“…The diagnostic delays observed in the studied patients are lower than those reported from EMR and countries of origin of the patients [7][8][9][10][11][12][13]. A systematic review of the Indian literature found that the patient, diagnostic and treatment delay were 18.4, 31.0 and 2.5 days, respectively, and the median total delay of 55.3 days [14].…”
Section: Discussionmentioning
confidence: 81%